Racing to the Bottom? Foreign Investment and Air Pollution in Developing Countries - Wheeler, David (World Bank, Washington, DC, 2014)
Critics of free trade have raised the specter of a "race to the bottom," in which environmental standards collapse because polluters threaten to relocate to "pollution havens" in the developing world. Proponents of this view advocate high, globally uniform standards enforced by punitive trade measures that neutralize the cost advantage of would-be pollution havens. To test the race-to-the-bottom model, the author analyzes recent air quality trends in the United States and in Brazil, China, and Mexico, the three largest recipients of foreign investment in the developing world. The evidence clearly contradicts the model's central prediction. The most dangerous form of air pollution--suspended particulate matter--has actually declined in major cities in all four countries during the era of globalization. Citing recent research, the author argues that the race-to-the-bottom model is flawed because its basic assumptions misrepresent the political economy of pollution control in developing countries. He proposes a more realistic model, in which low-income societies serve their own long-run interests by reducing pollution. He concludes with recommendations for international assistance measures that can improve environmental quality without counterproductive enforcement of uniform standards and trade sanctions.